Hubungan antara Kepatuhan Pengobatan dengan Kadar Gula Darah pada Penderita Diabetes Mellitus Tipe 2 Di Wilayah Kerja Puskesmas Kota Samarinda - Putri, Natasya Valentin; Septiawan, Taufik (Poltekkes Kemenkes Palembang, 2025)
Background : Diabetes is a disease with metabolic disorders that make blood sugar levels above normal. Factors that can affect blood sugar levels are medication adherence, treatment adherence plays an important role in maintaining blood sugar levels in the normal range. Objective : To determine the relationship between medication adherence and blood sugar levels in patients with type 2 diabetes mellitus. Method : Quantitative with a cross sectional approach, a sample of 174 people was determined by random sampling. The research instrument used the Medication Adherence Scale-8 questionnaire as a measure of medication adherence and a glucometer as a measure of blood sugar levels. Test bivariate analysis using the Chi-Square test. Results : Of the 174 respondents, it was found that the majority of patients with moderate medication adherence were 82 people (46.9%). out of 174 respondents the majority of results with normal blood sugar levels were 88 people (50.3%) and with abnormal blood sugar levels were 87 people (49.7%). Statistical results obtained p value = 0.002 < α (0.05) there is a relationship between adherence to treatment of blood sugar levels in patients with type 2 diabetes mellitus. Conclusion : There is a relationship between medication adherence and blood sugar levels in patients with type 2 diabetes mellitus in the working area of ​​the Pasundan Public Health Center, Samarinda Ulu.